The neural correlates of visual imagery vividness – An fMRI study and literature review. (August 2018) - Fulford, Jon; Milton, Fraser; Salas, David; Smith, Alicia; Simler, Amber; Winlove, Crawford; Zeman, Adam
Abstract: Using the Vividness of Visual Imagery Questionnaire we selected 14 high-scoring and 15 low-scoring healthy participants from an initial sample of 111 undergraduates. The two groups were matched on measures of age, IQ, memory and mood but differed significantly in imagery vividness. We used fMRI to examine brain activation while participants looked at, or later imagined, famous faces and famous buildings. Group comparison revealed that the low-vividness group activated a more widespread set of brain regions while visualising than the high-vividness group. Parametric analysis of brain activation in relation to imagery vividness across the entire group of participants revealed distinct patterns of positive and negative correlation. In particular, several posterior cortical regions show a positive correlation with imagery vividness: regions of the fusiform gyrus, posterior cingulate and parahippocampal gyri (BAs 19, 29, 31 and 36) displayed exclusively positive correlations. By contrast several frontal regions including parts of anterior cingulate cortex (BA 24) and inferior frontal gyrus (BAs 44 and 47), as well as the insula (BA 13), auditory cortex (BA 41) and early visual cortices (BAs 17 and 18) displayed exclusively negative correlations. We discuss these results in relation to a previous, functional imaging study of a clinical case of 'blind imagination', and to the existing literature on the functional imaging correlates of imagery vividness and related phenomena in visual and other domains.